(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: December 9, 2016 is the day of the General Election of Regional Head simultaneously throughout Indonesia. One of the areas that implement Regional Head Election is the province of North Sulawesi. Based on the results study Bawaslu North Sulawesi there are many districts / municipalities in North Sulawesi were prone to problems in the Regional Head General Election. From the results of this study Southeast Minahasa is a region prone to 4th highest problems in the process of Regional Head General Election. In addition to money politics, the neutrality of the State Civil Apparatus is one of the most common problems occur in the Regional Head General Election in Southeast Minahasa Regency. Recognized by one of the State Civil Apparatus that violations do is follow the campaign with the party attributes and participate in supervising the voting results on Election Day took place. This happens because there is intervention from the employer to the chief of the District is forwarded to the State Civil Apparatus in each office. As for the purpose of this research was to determine how the neutrality of the State Office of Administrative Civil Secretariat Southeast Minahasa regency in the election of Governor and Vice Governor of North Sulawesi province in 2015 The research method in this study is qualitative research methods and data collection techniques in this study is the observation / direct observation of localized research, conduct interviews, and documentation. The results showed there were several State Civil Apparatus 2015 that violated the rules on the election in the area. The factors that influence that the State violated the Civil Aparatur Regional Head Election process takes place is a rule which does not provide clear boundaries between political and administrative domain, the intervention of political parties, and individual interests. Keywords: Neutrality Civil State Apparatus, the election of Governor and Vice Governor